Voluntary intake and livestock productivity in different ecological zones of Africa - Dicko, M.S.; Lambourne, L.J.; Leeuw, P.N. de; Haan, Cees de (International Livestock Centre for Africa, 1981)
Describes methods used to determine the voluntary intake, grazing behaviour & productivity of livestock in sedentary or semi-transhumant grazing systems of the Malian Sahel, defining relations between intake & some environmental factors, & relating some of the results obtained to other ecological zones in Tropical Africa; with particular reference to weight changes of cattle & their relation to intake, forage availability & implications of the value of protein content for animal production improvement.